Metallocorroles as Nonprecious‐Metal Catalysts for Oxygen Reduction. Issue 47 (2nd October 2015) - Levy, Naomi; Mahammed, Atif; Kosa, Monica; Major, Dan T.; Gross, Zeev; Elbaz, Lior
Abstract: The future of affordable fuel cells strongly relies on the design of earth‐abundant (non‐platinum) catalysts for the electrochemical oxygen reduction reaction (ORR). However, the bottleneck in the overall process occurs therein. We have examined herein trivalent Mn, Fe, Co, Ni, and Cu complexes of β‐pyrrole‐brominated corrole as ORR catalysts. The adsorption of these complexes on a high‐surface‐area carbon powder (BP2000) created a unique composite material, used for electrochemical measurements in acidic aqueous solutions. These experiments disclosed a clear dependence of the catalytic activity on the metal center of the complexes, in the order of Co>Fe>Ni>Mn>Cu. The best catalytic performance was obtained for the Co III corrole, whose onset potential was as positive as 0.81 V versus the reversible hydrogen electrode (RHE). Insight into the properties of these systems was gained by spectroscopic and computational characterization of the reduced and oxidized forms of the metallocorroles. Abstract : Money‐saving measures : A series of first‐row transition‐metal corroles were investigated as electrocatalysts for the oxygen reduction reaction (ORR). The best catalytic performance was obtained for the Co III corrole, which had an onset potential of 0.81 V versus the reversible hydrogen electrode (RHE), comparable to the performance of precious‐metal catalysts used by the fuel‐cell industry. Br red, N dark blue, C light blue.